STRATEGY OF SEGMENTING, TARGETING AND POSITIONING IN MARKETING F&B PRODUCT AT FOX HOTEL PEKANBARU - Dwi Fitria Wulandari; Musadad " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In the world of tourism industry at this time especially competition between the hospitality industry is increasingly fierce and tight. One company in the hotel industry named Fox Hotel Pekanbaru also faces increasingly fierce and fierce competition with various hospitality industry competitors in the city of Pekanbaru. Therefore, this research aims to describe the marketing strategy of the F&B product (Segmenting, Targeting and Positioning) from Fox Hotel Pekanbaru and analyze its application. Collecting research data through observation, interviews and documentation with management and through data sources in the form of archives and documents owned by Fox Hotel Pekanbaru relating to this research. Analysis results show that Fox Hotel Pekanbaru from a segmenting perspective uses the geographic segmenting, demographic segmenting and psychographic segmenting. From a targeting perspective, Fox Hotel Pekanbaru uses a differeniated targeting strategy and also focuses on F&B event, promotions, a la carte and indonesian food signature. Whereas from a positioning perspective, Fox Hotel Pekanbaru uses the basis of competitors, price, quality and  in determining the market position of Fox Hotel Pekanbaru also takes positioning steps.  Keywords: Segmenting, Targeting, Positioning, F&B Product